Perfusion imaging and clinical outcome in acute minor stroke with large vessel occlusion - Seners, Pierre; Nagel, Simon; Potreck, Arne (Stroke, 2022)
Background: - - Whether bridging therapy (intravenous thrombolysis [IVT] followed by mechanical thrombectomy) is superior to IVT alone in minor stroke with large vessel occlusion is unknown. Perfusion imaging may identify subsets of large vessel occlusion-related minor stroke patients with distinct response to bridging therapy. - - Methods: - - We conducted a multicenter international observational study of consecutive IVT-treated patients with minor stroke (National Institutes of Health Stroke Scale score ≤5) who had an anterior circulation large vessel occlusion and perfusion imaging performed before IVT, with a subset undergoing immediate thrombectomy. Propensity score with inverse probability of treatment weighting was used to account for baseline between-groups differences. The primary outcome was 3-month modified Rankin Scale score 0 to 1. We searched for an interaction between treatment group and mismatch volume (critical hypoperfusion-core volume). - - Results: - - Overall, 569 patients were included (172 and 397 in the bridging therapy and IVT groups, respectively). After propensity-score weighting, the distribution of baseline variables was similar across the 2 groups. In the entire population, bridging was associated with lower odds of achieving modified Rankin Scale score 0 to 1: odds ratio, 0.73 [95% CI, 0.55-0.96]; P=0.03. However, mismatch volume modified the effect of bridging on clinical outcome (Pinteraction=0.04 for continuous mismatch volume); bridging was associated with worse outcome in patients with, but not in those without, mismatch volume <40 mL (odds ratio, [95% CI] for modified Rankin Scale score 0-1: 0.48 [0.33-0.71] versus 1.14 [0.76-1.71], respectively). Bridging was associated with higher incidence of symptomatic intracranial hemorrhage in the entire population, but this effect was present in the small mismatch subset only (Pinteraction=0.002). - - Conclusions: - - In our population of large vessel occlusion-related minor stroke patients, bridging therapy was associated with lower rates of good outcome as compared with IVT alone. However, mismatch volume was a strong modifier of the effect of bridging therapy over IVT alone, notably with worse outcome with bridging therapy in patients with mismatch volume ≤40 mL. Randomized trials should consider adding perfusion imaging for patient selection.
Originally published 12 Jul 2022
Gesehen am 09.02.2023